Analysis of Community Satisfaction Through Administrative Services - Isgunandar, Isgunandar; Asriana, Asriana; H, Nasaruddin; Suprianto, Suprianto (Universitas Negeri Makassar, 2023)
Service quality is a condition where a dynamic relationship is created between users and service providers. This research aims to determine the views or perceptions of the community in receiving administrative services at the Pattaneteang Village Office, Dusun Bungeng, Bantaeng Regency. Using descriptive qualitative research with the type of field research. Researchers use data collection techniques through observation, interviews, and documentation. Primary data used includes the Village, Village staff, and the community. Meanwhile, secondary data is data sourced from the Village Office which is related to the research. The research results found that the benchmark indicators for satisfaction are simplicity, certainty of time, completeness of facilities and infrastructure, then access and discipline. The influencing factors are supporting factors with the existence of guidelines for implementing administration, as well as being supported by data-based village development innovations and digital maps which make it easier for village officials to publish village books. Meanwhile, the inhibiting factors are limited facilities and infrastructure and low public awareness of the importance of completing personal identity documents. This research can be used as a reference for knowledge, and understanding, and also a benchmark in knowing the community's views on receiving administrative services in Pattaneteang Village. The service process at the Pattaneteang Village office applies a digitalization system. Of course, this is unique considering that the label